Attentional Capture and Inhibition of Saccades after Irrelevant and Relevant Cues. (22nd April 2014) - Priess, Heinz-Werner; Heise, Nils; Fischmeister, Florian; Born, Sabine; Bauer, Herbert; Ansorge, Ulrich
Abstract : Attentional capture is usually stronger for task-relevant than irrelevant stimuli, whereas irrelevant stimuli can trigger equal or even stronger amounts of inhibition than relevant stimuli. Capture and inhibition, however, are typically assessed in separate trials, leaving it open whether or not inhibition of irrelevant stimuli is a consequence of preceding attentional capture by the same stimuli or whether inhibition is the only response to these stimuli. Here, we tested the relationship between capture and inhibition in a setup allowing for estimates of the capture and inhibition based on the very same trials. We recorded saccadic inhibition after relevant and irrelevant stimuli. At the same time, we recorded the N2pc, an event-related potential, reflecting initial capture of attention. We found attentional capture not only for, relevant but importantly also for irrelevant stimuli, although the N2pc was stronger for relevant than irrelevant stimuli. In addition, inhibition of saccades was the same for relevant and irrelevant stimuli. We conclude with a discussion of the mechanisms that are responsible for these effects.